2017
DOI: 10.1371/journal.pone.0172809
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of multiplex PCR methods and respiratory viruses’ distribution in children below 15 years old according to age, seasons and clinical units in France: A 3 years retrospective study

Abstract: BackgroundTo date, only influenza and RSV testing are recommended for respiratory viruses’ detection in paediatric units. In this study, we described, according to seasons, ages and clinical units, the results obtained in children (<15 years old) by multiplex-PCR (mPCR) tests allowing a quick and wide range detection of all respiratory viruses. These results were also compared with RSV specific detection.MethodsAll nasopharyngeal mPCR and RSV tests requested by clinicians in our French teaching hospitals group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
7
21
1
Order By: Relevance
“…Our present results emphasized the great variations in the positivity rate and viral distribution from one age group to another, and confirmed some of previous observations made in France [10] whereby very young children (under the age of 1 month) had lower positivity and viral coinfection rates than older children. However, the picornaviruses (EVs/hRVs) were most frequent in all age groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present results emphasized the great variations in the positivity rate and viral distribution from one age group to another, and confirmed some of previous observations made in France [10] whereby very young children (under the age of 1 month) had lower positivity and viral coinfection rates than older children. However, the picornaviruses (EVs/hRVs) were most frequent in all age groups.…”
Section: Discussionsupporting
confidence: 92%
“…The application of new multiplex PCR assays has provided new insights into the epidemiology of viral respiratory infections in children and adults [9][10][11][12][13]. However, some situations have yet to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of the burden of respiratory viruses in hospital settings remain to be investigated. In pediatric populations, in which respiratory virus pathogenicity has been well demonstrated for some viral groups, rapid mPCR assays have been shown to improve the detection of respiratory viruses and to decrease the time required to obtain results, thereby making it possible to decrease the duration of antibiotic treatment or the time spent in the emergency department [25,48]. In adults, evidence for the pathogenicity of respiratory viruses is increasingly evidenced [6,[19][20][21][22][23], but antibiotic treatment is often continued after positive PCR tests for viruses, even with a normal chest radiography; further studies and new recommendations are therefore required today [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inconsistencies in the evidence, there are some further limitations to these guidelines. PREDICT focuses on the outcomes of hospital admission, length of stay, intensive care admission and death but does not discuss other clinically relevant outcomes such as the reduction of interventions, including antibiotic use, chest radiography and blood and urine investigations, which may represent a potential benefit of routine viral testing . A recent meta‐analysis demonstrated that the use of rapid viral testing in acute respiratory illness in children reduced the rate of chest radiography, while the evidence was not conclusive regarding the reduction of other invasive investigations or antibiotics, and further research is needed .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent progress on RSV vaccines emphasises the need for better characterisation of the burden of RSV disease in Australia to support assessment of their possible cost‐effectiveness in the future . Finally, routine viral testing may have a role in the surveillance of emerging respiratory epidemics of public health importance …”
Section: Discussionmentioning
confidence: 99%